INTEGRASI NILAI ADAT KASADA DALAM PENDIDIKAN MIGITASI BENCANA TERPADU (Pendekatan Holistik untuk Membentuk Kesadaran Bencana Sejak Dini) - khoiriyah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Integrated disaster mitigation education was first developed in Sendai, Japan, with the aim of creating disaster-resilient schools. This approach emphasizes active community involvement and employs a bottom-up method that integrates local wisdom, scientific approaches, and student centered active learning. Teachers play a crucial role in designing learning activities based on local cultural values. However, its implementation in the field remains limited and is still largely dominated by conventional natural science approaches. Therefore, government initiatives particularly from the Ministry of Religious Affairs are needed to develop a disaster mitigation curriculum rooted in local values, especially at the Madrasah Ibtidaiyah (Islamic elementary school) level. This study aims to explore the Islamic spiritual values embedded in the Kasada ritual of the Tengger community, which are relevant to disaster mitigation efforts related to the volcanic activity of Mount Bromo. The research was conducted at MI Muhammadiyah Pendil in Probolinggo Regency, involving traditional leaders, educators, and madrasa supervisors. The approach used is qualitative-interpretative with a grounded theory methodology. The expected outcome is the development of a disaster mitigation learning model that integrates Islamic spiritual values and Kasada cultural traditions into the school curriculum, along with teacher training programs to strengthen their capacity to deliver disaster education grounded in spirituality and local wisdom.